LC-ESI-MS/MS determination of oxyhalides (chlorate, perchlorate and bromate) in food and water samples, and chlorate on household water treatment devices along with perchlorate in plants. (November 2019) - Constantinou, Panayiotis; Louca-Christodoulou, Despo; Agapiou, Agapios
Abstract: The results of the validation study of the LC-ESI-MS/MS method for the determination of chlorate (ClO3 − ), perchlorate (ClO4 − ) and bromate (BrO3 − ) in water and food samples are summarized. Towards this, 284 samples of drinking water were analysed, out of which the 69% contained chlorate above the limit of quantitation (LOQ) of 0.01 mg/L, with maximum amount of 1.1 mg/L. Only 6 samples were found to be positive with perchlorate at levels <0.01 mg/L. Bromate was detected in 5 drinking water samples at levels above the LOQ, at concentrations up to 0.026 mg/L. For the validation of the method in food, 108 blank samples were spiked with chlorate and perchlorate for the LC-MS/MS analysis at two levels. In total 247 food samples from the market of 19 different commodities including fruits, vegetables, cereals and wine, were analysed. The maximum concentration of chlorate was found at 0.83 mg/kg in a sample of cultivated mushrooms. The number of samples contaminated with perchlorate was also small, with all the determined concentrations below the LOQ of 0.05 mg/kg. Experiments for the chlorate reduction in drinking water, showed that reverse osmosis treatment is effective in particular with newly installed cartridges. Finally, according to the results of the pilot study when chlorinated water is used for the plant irrigation, accumulation of chlorate is observed, especially in the green parts of the plant. Perchlorate was also detected in leafy samples, although it was not present in the irrigation water. Graphical abstract: Image 1023921 Highlights: Oxyhalides determination in food and drinking water was performed by LC-ESI-MS/MS. 90% of drinking water samples contained chlorate; many above the regulatory limits. Household water treatment devices except reverse osmosis failed to remove chlorate. Market food samples do not contain chlorate if irrigation water is not chlorinated. Chlorinated water irrigation leads to chlorate and perchlorate accumulation in plants.